Trimethylamine-N-Oxide levels are similar in asymptomatic vs. symptomatic cerebrovascular atherosclerosis - Heyse, Miriam; Tunkl, Christine; Drüschler, Katharina; Berberich, Anne; Zorn, Markus; Ringleb, Peter A.; Okun, Jürgen G.; Mundiyanapurath, Sibu (Frontiers in neurology, 2021)
Abstract: Introduction: Trimethylamine-N-oxide (TMAO) is correlated with atherosclerosis and vascular diseases as coronary heart disease and ischemic stroke. The aim of the study was investigate whether TMAO levels are different in symptomatic vs. asymptomatic cerebrovascular atherosclerosis. Methods: This was a prospective, case-control study, conducted at a tertiary care university hospital. Patients were included if they had large-artery atherosclerosis (TOAST criteria). Symptomatic patients with ischemic stroke were compared with asymptomatic patients. As primary endpoint, TMAO levels on admission were compared between symptomatic and asymptomatic patients. Univariable analysis was performed using Mann-Whitney-U test and multivariable analysis using binary logistic regression. TMAO values were adjusted for glomerular filtration rate (GFR), age and smoking. Results: Between 2018 and 2020, 82 symptomatic and asymptomatic patients were recruited. Median age was 70 years, 65% were male. Comparing symptomatic (n=42) and asymptomatic (n=40) patients, no significant differences were found in univariable analysis in TMAO (3.96 [IQR 2.30-6.73] vs. 5.36 [3.59-8.68] μmol/l; p=0.055), GFR (87 [72-97] vs. 82 [71-90] ml/min*1.73m2; p=0.189) and age (71 [60-79] vs. 69 [67-75] years; p=0.756). In multivariable analysis TMAO was not a predictor of symptomatic cerebrovascular disease after adjusting for age and GFR (OR 1.003 [95% CI: 0.941-1.070]; p=0.920). In a sensitivity analysis, we only analyzed patients with symptomatic stenosis and excluded patients with occlusion of brain-supplying arteries. Again, TMAO was not a significant predictor of symptomatic stenosis (OR 1.039 [0.965-1.120], p=0.311). Conclusion: TMAO levels could not be used to differentiate between symptomatic and asymptomatic cerebrovascular disease in our study.
Gesehen am 04.05.2021